Iron overload leading to cirrhosis in a patient with hereditary spherocytosis and heterozygosity for H63D mutation in the HFE gene - M. C. P. Madurapperuma; R . B. A. T. Dulanjalie; T. M. H. M. Thennakoon; K. W. Gunawardena; W. W. L. A. Jayanaga; V. H. W. Dissanayake (Sri Lanka College of Internal Medicine, 2023)
Hereditary spherocytosis (HS) refers to a group of autosomal dominantly inherited heterogeneous hereditary haemolytic anaemias (HHA). Significant iron overload in HS is uncommon. Iron overload has been described as a complication of HS when there is co-inheritance of hereditary haemochromatosis (HH). H63D mutation accounts for a minority of hereditary hemochromatosis cases and does not cause iron overload in an otherwise healthy heterozygous carrier state. We present a 64-year-old man , diagnosed with HS presenting with cirrhosis without significant on-going haemolysis. He had a markedly high serum ferritin and transferrin saturation. Magnetic Resonance Imaging for liver iron concentration revealed haemochromatosis of the liver. HFE genotyping showed heterozygosity for the H63D mutant allele. Haemolysis in HS does not usually result in clinically significant iron excess leading to haemochromatosis and the presence of H63D heterozygous mutation will increase the risk of clinically significant iron overload which can lead to hepatic iron deposition and fibrosis. Therefore, if a patient with H63D mutation demonstrates clinically significant iron overload, clinicians should search for other factors that increase iron excess such as on-going haemolysis, alcohol abuse and presence of metabolic syndrome.